Design and development of IV fluid warming system using TRIZ methodology. (1st March 2023) - Shrivastava, Siddhant; Verma, Abhishek; Ramkumar, Janakarajan
Abstract: In intravenous (IV) tube infusion therapy, various fluids, such as saline, glucose, blood, and others, are infused into the body via the veins leading to the heart, causing the fluids to circulate throughout the body. The IV fluid is packaged in a flexible plastic-based container, and during therapy, the container is kept in an open environment that could either cool or warm the fluid. The body's core temperature, which is usually 37 °C, catastrophic drops when this cool intravenous fluid is combined with blood, resulting in hypothermia and other health complications. It can be life-threatening for young newborns, severe patients, and elderly individuals. Nearly 14% of hospitalized patients are hypothermic upon arrival. In this study, a portable IV fluid warming system was made that warms the intravenous fluids before they reach the human body, preventing hypothermia by maintaining the required temperature. The solution was formulated using the TRIZ contradiction matrix. Various processes involved in resolving the conflict via the TRIZ matrix were investigated in depth, and the device was subsequently made employing the ideas. The device consists of an encased heating jacket that can be wrapped all around the IV fluid container to heat the fluid without direct contact, thereby eliminating the risk of contamination. It works on a feedback control system & simplifies temperature regulation desired by the physician. The design was validated via thermal analysis in software, and via experimentation, both the results were within a close tolerance of each other, which proves the design successful. Later, the equipment was certified by an ISO 13485-accredited facility, and currently, testing is ongoing in hospitals under supervision. The developed IV fluid warmer is cost-effective, recyclable, and ergonomically designed for user comfort compared to conventional commercial warmers.